Respuesta :
–6x3 + 4x2 – 4x = -(–6x3 + 4x2 – 4x)
=6x3 - 4x2 + 4x
answer is B)6x^3 – 4x^2 + 4x
=6x3 - 4x2 + 4x
answer is B)6x^3 – 4x^2 + 4x
Answer:
B. [tex]6x^3 - 4x^2 + 4x[/tex]
Step-by-step explanation:
Since, the additive inverse of an expression or a number is an expression or number that after addition gives the additive identity '0'.
Let x be the additive inverse of the polynomial [tex]-6x^3+4x^2-4x[/tex],
By the above statement,
[tex](-6x^3+4x^2-4x)+x = 0[/tex]
[tex]x = -(-6x^3+4x^2-4x)[/tex]
[tex]x=6x^3-4x^2+4x[/tex]
Hence, the additive inverse of the polynomial [tex]-6x^3+4x^2-4x[/tex] is [tex]6x^3-4x^2+4x[/tex]
Option B is correct.